Development of Research Competences in University Professors: A Bibliographic Review - Sernaqué, Manuel Antonio Cardoza; Luis, Montenegro Camacho; Alarcon, Mercedes Alejandrina Collazos; Farías, Víctor Alejandro García; Valdiviezo, Omar Bellido; Chávez, Jairo Jaime Turriate (International Journal of Membrane Science and Technology, 2023)
The research aimed to analyze the contribution of scientific publications regarding the study of the development of research skills in university professors. The bibliographic review and documentary analysis of scientific articles published in different scientific databases were used as a study method. For the theoretical approach regarding the definition, importance and classification of research competences in university professors, the contributions of researchers who have published scientific articles in different databases were used; and for the study of background, the articles published in the Scopus database between 2018 and 2022 were used as a source of information. It was concluded that there are different studies that address the importance of developing their research skills in university teachers, which are associated with the improvement of their professional profile, teaching conditions in the training of professionals and their contribution to increasing the scientific production of universities through the formulation of scientific research and technological development projects and the publication of scientific articles in academic databases.